Jurisdictional Boundaries of the Unified Patent Court: An analysis of the Judgment of the Düsseldorf Local Division in case UPC_CFI_355/2023 - Giordano, Jacopo (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
This note examines the jurisdictional architecture of the Unified Patent Court (UPC), focusing on the interaction between the Unified Patent Court Agreement (UPCA) and the Brussels I bis Regulation when asserting jurisdiction over European patents. The analysis centers on judgment UPC_CFI_355/2023 rendered by the Düsseldorf Local Division of the UPC, which raises questions about the limits of the UPC’s jurisdiction, especially in cases involving infringement of European patents validated in states not party to the UPCA. Moreover, the decision sheds light on the complex issue of validity challenges under Art. 24(4) of the Brussels I bis Regulation in infringement proceedings, especially in view of the recent ruling of the Court of Justice of the European Union (CJEU) in BSH Hausgeräte.
Keywords: European patent; patent infringement; Jurisdiction; Unified Patent Court